To question about psychological particularity of I-conception of junior age with a various orientation - A V Ivashchenko; L V Zubova; M N Grigoryeva (Peoples' Friendship University of Russia (RUDN University), 2009)
In clause some psychological features of an «I-conception» of junior-stage people with a various orientation of the person are presented.